A heterocycle fusing strategy for simple construction of efficient solution-processable pure-red thermally activated delayed fluorescence emitters. Issue 42 (12th October 2022) - Gong, Xu; Xiang, Yepeng; Ning, Weimin; Zhan, Lisi; Gong, Shaolong; Xie, Guohua; Yang, Chuluo
Abstract : A heterocycle fusing strategy is demonstrated to construct solution-processable red thermally activated delayed fluorescence emitters. The resulting pure-red organic light-emitting diodes deliver a high external quantum efficiency of 6.8%. Abstract : The development of solution-processable pure-red thermally activated delayed fluorescence (TADF) emitters remains a challenging task in the field of organic light-emitting diodes (OLEDs). Here two strong electron acceptor moieties, acenaphtho[1, 2- b ][1, 2, 5]oxadiazolo[3, 4- e ]pyrazine (ANOP ) and acenaphtho[1, 2- b ][1, 2, 5]thiadiazolo[3, 4- e ]pyrazine (ANTP ), were designed and synthesized by fusing 1, 2, 5-oxadiazole or 1, 2, 5-thiadiazole on an acenaphtho[1, 2- b ]pyrazine unit through a simple and catalyst-free dehydration cyclization reaction. Combined with rigid electron-donating units, 9, 9-dimethyl-9, 10-dihydroacridine (DMAC ) and 2, 7-dimethyl-10 H spiro[acridine-9, 9′-fluorene] (MeFAC ), four solution-processable pure-red TADF emitters, ANOP-DMAC, ANOP-MeFAC, ANTP-DMAC, and ANTP-MeFAC, were designed and prepared through catalyst-free nucleophilic substitution reactions. The rational molecular design principles endow all the emitters with small singlet-triplet energy gaps (Δ E ST ), prominent TADF character, red emission, and moderate Φ PL s. The optical, electrochemical, and film morphological properties of all the emitters were systematically investigated. As a consequence, the ANTP-DMAC -based OLED realized a maximum external quantum efficiency of 6.8% with a peak wavelength at 630 nm and Commission International de l'Eclairage 1931 (CIE1931) coordinates of (0.59, 0.40), which is among one of the highest device performances for solution-processed pure-red TADF OLEDs.